Trajectory linearization-based robust course keeping control of unmanned surface vehicle with disturbances and input saturation. (June 2021) - Qiu, Bingbing; Wang, Guofeng; Fan, Yunsheng
Abstract: This article addresses the problem of course keeping for unmanned surface vehicle (USV) subject to rudder servo characteristics, disturbances, uncertainties and rudder saturation. A double loop robust compound control strategy is developed by incorporating finite-time uncertainty observer (FUO) and auxiliary dynamic system into trajectory linearization control (TLC). TLC is an effective robust control technique with simple design structure, which is used in the course control experiment of USV for the first time. In each loop, the FUO and auxiliary system are designed to compensate unknown lumped disturbances and input saturation, respectively. A nonlinear tracking differentiator (NTD) is concurrently introduced to realize differentiation and filtering for the reference command. Strict stability analysis indicates that the entire system is uniformly ultimately bounded (UUB). Results from simulations and experiments are presented to validate the developed strategy. Highlights: An enhanced TLC with only two tuning parameters is introduced to design course keeping controller for USV, which is the first time applied to the actual USV test. The unknown lumped disturbances are handled online using FUO, and the rudder servo characteristics are better described by a second-order under-damped system replacing a traditional first-order inertial system. An auxiliary dynamic system that is governed by smooth switching function is developed to compensate for the saturation constraint on actuator. A novel robust FUO-based TLC strategy is developed for course keeping control of USV, and numerical simulation and experiment demonstrate remarkable performance.